Basin depth distribution in western Anatolia using EGM2008 gravity model - (:unkn) unknown (Geothermal Resources Council, 2014)
EGM2008 gravity model is used to generate a map of basin depth distribution in western Anatolia. Topographic and the crustal scale gravity effects were removed by applying appropriate 2-D filters. The resulting residual gravity map shows the basin depth distribution in western Anatolia. The results agree well with the locations of the currently exploited areas. Some of the areas with deep basins any no surface manifestations are also outlined as potential high temperature geothermal targets. Copyright © (2014) by the Geothermal Resources Council All right reserved.
Keywords: Basin depth; EGM2008; Geo-thermal systems; Gravimtery; Western Anatolia